2000
DOI: 10.1159/000012832
|View full text |Cite
|
Sign up to set email alerts
|

Changes of HDL Subfractions by Eicosapentaenoic Acid Intake and Physical Load in 20- to 25-Year-Old Men

Abstract: The effects of daily eicosapentaenoic acid (EPA) intake and physical activity on high-density lipoprotein (HDL) subfraction, which may be an index of health status, were examined. The HDL subfraction, triglyceride and T-chol levels in the serum of 10 male volunteers aged 20–25 were examined before, immediately after and 1 h after being subjected to a physical load by bicycle ergometer at 90 W for 20 min. Subjects were then given 1.25 g EPA/day for 2 weeks, and the above test was repeated. By EPA intake, the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…Our results suggest that n-3 PUFAs are associated with an increase in the relative proportion of the largest, least dense HDL 2b subspecies accompanied by a decrease in the smaller HDL 3a and HDL 3b subspecies. Similar results were observed in two previous small, short-term, intervention studies [38,39]. Sakamoto et al reported that the relative proportion of HDL 2b increased and that of HDL 3b and HDL 3c decreased significantly after 2 weeks of eicosapentaenoic acid (EPA) supplementation [38].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results suggest that n-3 PUFAs are associated with an increase in the relative proportion of the largest, least dense HDL 2b subspecies accompanied by a decrease in the smaller HDL 3a and HDL 3b subspecies. Similar results were observed in two previous small, short-term, intervention studies [38,39]. Sakamoto et al reported that the relative proportion of HDL 2b increased and that of HDL 3b and HDL 3c decreased significantly after 2 weeks of eicosapentaenoic acid (EPA) supplementation [38].…”
Section: Discussionsupporting
confidence: 82%
“…Similar results were observed in two previous small, short-term, intervention studies [38,39]. Sakamoto et al reported that the relative proportion of HDL 2b increased and that of HDL 3b and HDL 3c decreased significantly after 2 weeks of eicosapentaenoic acid (EPA) supplementation [38].…”
Section: Discussionsupporting
confidence: 82%
“…It is of interest that the effect of FLX feeding in birds, which increased plasma α‐linolenic acid and its longer‐chain derivatives, had an opposite effect on lipoprotein subfraction distributions compared with humans (Sakamoto et al., ). Male human subjects, aged 20–25 years, supplemented with 1.25 g/day tuna oil (25% eicosapentaenoic acid and 13% docosahexaenoic acid) for 2 weeks showed significantly decreased HDL 3c and HDL 3b and increased HDL 2b .…”
Section: Discussionmentioning
confidence: 99%
“…Male human subjects, aged 20–25 years, supplemented with 1.25 g/day tuna oil (25% eicosapentaenoic acid and 13% docosahexaenoic acid) for 2 weeks showed significantly decreased HDL 3c and HDL 3b and increased HDL 2b . In humans, this lipoprotein subfraction pattern is known as the longevity pattern and appears to be associated with a low risk of atherosclerosis (Sakamoto et al., ). However, in the present study, when Monk parrots were fed an α‐linolenic acid–enriched diet containing 10% ground FLX, the relative percentage of HDL 3c increased, while both the relative percentage and absolute amount of HDL 2b decreased and HDL 3b remained constant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation